Digitalne vsebine na razstavi Novo mesto 1848-1918 v Dolenjskem muzeju Novo mesto - Pungerčar, Majda (Knjižnica, 2012)
For the first time, the Dolenjska museum Novo mesto provided access to digitised museum resources when they took the decision to enrich the exhibition Novo mesto 1848-1918 by adding digital content . The following goals were identified: the digital content was created at the time of exhibition planning and design, it met the needs of different age groups of visitors, and during the exhibition the content was accessible via touch screen. As such, it also served for educational purposes (content-oriented lectures) or problem solving team work. In the course of exhibition digital content was accessible on the museum website http://www.novo-mesto 1848-1918.si. The digital content was divided into the following sections: the web photo gallery, the quiz and the game. The photo gallery was designed in the same way as the exhibition and the print catalogue and extended by the photos of contemporary Novo mesto and accompanied by the music from the orchestron machine. The following themes were outlined: the Austrian empire, the Krka and Novo mesto, the town and its symbols, images of the town and people, administration and economy, social life and Novo mesto today followed by digitised archive materials and sources from that period such as the Commemorative book of the Uniformed Town Guard, the National Reading Room Guest Book, the Kazina guest book, the album of postcards and the Diploma of Honoured Citizen Josip Gerdešič. The web application was also a tool for a simple and on line selection of digitised material and the creation of new digital content which proved to be much more convenient for lecturing than Power Point presentations. The quiz consisted of 40 questions relating to the exhibition theme and the catalogue. Each question offered a set of three answers only one of them being correct and illustrated by photography. The application auto selected ten questions and valued the answers immediately. The quiz could be accessed individually or in a group of visitors as a quick test at the end of a visit to the exhibition. The computer game Cray Fish Hunting on the River of Krka was tailored to young visitours. It described the geographical position of Novo mesto on the Krka peninsula and some objects on the riverside (wooden baths, the old bridge, the dam and the mill). Hunting noble cray-fish was very extensive in the Novo mesto region untill the outburst of the cray-fish plague. It is said that up to 100,000 cay fish were caught annually and transported to all major towns of the then Austrian emire. The original museum collections were preserved by scanning precious items which were kept in depots. Digitised materials accessible on the museum website met the needs of the majority of users and provided expanded access to the museum collection through presentation of graphic materials in virtual exhibition on the web which was much more comprehensive than a printed catalogue. There was also the possibility of remote access to the museum website which was very important for tourists and museum visitors with special needs. It was possible to design customer tailored presentations on specific themes (postcards from the period of national awakening, local societie, middle class garments etc.). Digital content was also available to school teachers to discuss the themes of interest with their pupils or students either before or after visiting the exhibition. There are many pitfalls and limitations of digitisation, the biggest two being staff deficiency and shrinking budget. Furthermore, there are difficulties with the technical support, gathering information on the implementation process, seeking partners to digitise materials etc. Besiders, the question of long term digital archiving is of vital importance.
Keywords: razstave; photography; fotografija; digitalna fotografija; fotogalerije; digitalizacija; digitization; muzejske zbirke; muzeji; Dolenjski muzej; Novo mesto